Correct determination of the enhancement curve is critical to ensure accurate diagnosis using the Kaiser score as a clinical decision rule for breast MRI. Issue 138 (May 2021) - Grippo, Cristina; Jagmohan, Pooja; Helbich, Thomas H.; Kapetas, Panagiotis; Clauser, Paola; Baltzer, Pascal A.T.
Highlights: Correct determination of the initial enhancement time point critically influences the results of curve type analysis in breast MRI. Enhancement in the first post-contrast series may be too weak in case of short injection delay or individual circulation delay. Determining the enhancement curve using peak early uptake as initial enhancement reference ensures high sensitivity of the Kaiser score. Abstract: Objectives: the Kaiser score is increasingly recognized as a valuable tool to improve breast MRI interpretation. Contrast enhancement kinetics are the second most important diagnostic criterion, thus defining the curve type plays a crucial role in Kaiser score assessment. We investigate whether the timepoint used to determine the initial enhancement (early or peak) for the signal-intensity time curve analysis affects the diagnostic performance of the Kaiser score. Methods: This IRB-approved, retrospective, single-center study included 70 consecutives histologically verified breast MRI cases. Two off-site breast radiologists independently read all examinations using the Kaiser score, assessing the initial enhancement using three approaches: -first (1 st), second (2nd) and peak (maximum) of either 1 st or 2nd post-contrast timepoints. The initial enhancement was then compared to the last timepoint (delayed enhancement) to determine the curve type. Visual assessment of curve types was used for this study. Diagnostic performance was evaluated by receiver operating characteristics (ROC) analysis. Results: Kaiser score reading results using the peak enhancement of either the first or second timepoint performed significantly better than the other approaches (P < 0.05, respectively) and specifically achieved higher sensitivity. Diagnostic accuracy (AUC area under the curve) ranged between 85.4 % and 91.6 %, without significant differences between the two readers (P < 0.5). Conclusions: Diagnostic performance of the Kaiser score is significantly influenced by how the initial enhancement timepoint is determined. Peak enhancement should be used as initial timepoint to avoid pitfalls due to timing or physiological differences.